Analysis of Public Policy Implementation in the Decentralized System of Government in Indonesia - Rinaldi Akhmad; Aminullah Aminullah (Kajian Administrasi Publik dan ilmu Komunikasi, 2026)
Indonesia's decentralized policy was introduced as a strategic reform to improve public service delivery, strengthen local democracy, and enhance government responsiveness to regional needs. However, the implementation of public policies within a decentralized governance system continues to face various challenges that affect policy effectiveness and development outcomes. This study aims to analyze the implementation of public policy within Indonesia's decentralized governmental system and identify the major obstacles encountered by local governments in carrying out policy mandates. The research employs a qualitative approach using a literature review method by examining academic journals, government regulations, and relevant scholarly publications related to decentralization and public policy implementation. The findings indicate that disparities in regional capacity, overlapping authority between central and local governments, limited bureaucratic resources, weak intergovernmental coordination, and governance issues remain significant barriers to effective policy implementation. While decentralization has provided greater opportunities for local innovation and community participation, its outcomes vary significantly across regions due to differences in institutional readiness and administrative capability. The study concludes that strengthening local government capacity, improving coordination mechanisms, enhancing accountability systems, and ensuring regulatory consistency are essential for achieving effective policy implementation in a decentralized governance framework. These measures are expected to support better public services and more equitable regional development throughout Indonesia.